Gendered constraints to smallholder pig farming and marketing in Rwanda - Ouma, Emily; Ntawubizi, Martin; Achandi, Esther (2025)
The pig value chain in Rwanda holds great potential and can contribute to economic development and transformation in the country. However, several constraints impede pig production and marketing by smallholder farmers. This study was conducted as part of the, “Profiting from pigs in Rwanda” project led by the International Livestock Research Institute (ILRI) in partnership with the Rwanda Agricultural and Animal Resources Development Board (RAB), the University of Rwanda, Land O’Lakes Venture37, Orora Wihaze Activity, and the Rwanda Pig Farmers Association. The project aimed to improve the livelihoods of smallholder men and women pig producers, sustainably, through increased productivity and incomes and strengthened market linkages in pig value chains. This study component adopted a qualitative methodology through 8 Focus Group Discussions (FGDs) and 24 Key Informant Interviews (KIIs) in Gakenke and Nyamagabe districts in Rwanda. The data covered aspects of decision making over engagement in piggery, use of resources such as land, labour, and capital as well as access to veterinary services, supporting productivity improvements. These data highlight the overall constraints to smallholder pig production and marketing and the gender differences in these constraints. The data can be used to explore gendered constraints, uncover possible gendered opportunities in the pig value chains and guide the design of gender inclusive interventions for pig production and marketing.